Microporosity in carbon blacks - Stoeckli, Fritz; Guillot, André; Slasli, Abdou; Hugi-Cleary, Deirdre (My University, 2002)
Microporous carbon blacks can be characterized by the same techniques as activated carbons, using the classical DR equation and comparison plots based on non-porous materials. The CO2 adsorption isotherm at 273 K, combined with computer modelling, also leads to an assessment of microporosity. The results agree with independent techniques such as immersion calorimetry into liquids of variable molecular dimensions and a modified Dubinin equation. The study also confirms that the comparison plots based on N2 (77 K), CO2 (273 K) and C6H6 (293 K) do not necessarily lead to overlapping results for the total micropore volume and the external surface area of the carbons.
Keywords: A. carbon black; C. adsorption; modelling; D. porosity